Bioavailability of docosahexaenoic acid 22:6(n-3) from enantiopure triacylglycerols and their regioisomeric counterpart in rats. (15th June 2019) - Linderborg, Kaisa M.; Kulkarni, Amruta; Zhao, Ai; Zhang, Jian; Kallio, Heikki; Magnusson, Johann D.; Haraldsson, Gudmundur G.; Zhang, Yumei; Yang, Baoru
Highlights: DHA was efficiently absorbed in Sprague-Dawley rats with mild n-3 deficiency. No significant differences in the absorption between DHA in sn -1 and sn -3 positions. Less fecal DHA from the sn -2 position compared with the sn -1 and sn -3 positions. 5-Day intervention enough to modify the fatty acid profile of plasma phospholipids. Abstract: Lack of synthetic enantiospecific triacylglycerols (TAGs) has hindered our understanding of the impact of TAG structure on the absorption and metabolic fate of fatty acids (FAs). In a five-day feeding trial with mildly (n-3) deficient rats, the bioavailability of docosahexaenoic acid [22:6(n-3), DHA] and stearic acid (18:0) from the two different enantiomers of TAG: sn -22:6(n-3)-18:0-18:0 and sn -18:0-18:0-22:6(n-3), and their regioisomeric TAG: sn -18:0-22:6(n-3)-18:0 was compared. Less secretion of fecal DHA was detected from the sn -2 position compared with the sn -1 and sn -3 positions, but no difference was found in DHA content of the fasting plasma or in the weight of the body or organs. 18:0 was lost to feces mainly as cleaved from the primary positions but also as glycerol-bound. The 5-day intervention in rats was long enough to modify the fatty acid profile of plasma phospholipids.